2011
DOI: 10.1109/tnsre.2010.2078516
|View full text |Cite
|
Sign up to set email alerts
|

Taking NIRS-BCIs Outside the Lab: Towards Achieving Robustness Against Environment Noise

Abstract: Abstract-This paper reported initial findings on the effects of environmental noise and auditory distractions on the performance of mental state classification based on near-infrared spectroscopy (NIRS) signals recorded from the prefrontal cortex. Characterization of the performance losses due to environmental factors could provide useful information for the future development of NIRS-based brain-computer interfaces that can be taken beyond controlled laboratory settings and into everyday environments. Experim… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
50
0
2

Year Published

2012
2012
2023
2023

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 66 publications
(54 citation statements)
references
References 59 publications
2
50
0
2
Order By: Relevance
“…All auditory and visual distractions were suppressed as much as possible by the earmuffs and blindfold. If BCI technologies are to be used in everyday settings, however, movement artifacts [10], auditory and visual distractions [42], and mind-wandering still have to be detected and accounted for (e.g., as in [19]). Additionally, experimental sessions lasted less than one hour.…”
Section: Study Limitationsmentioning
confidence: 99%
See 1 more Smart Citation
“…All auditory and visual distractions were suppressed as much as possible by the earmuffs and blindfold. If BCI technologies are to be used in everyday settings, however, movement artifacts [10], auditory and visual distractions [42], and mind-wandering still have to be detected and accounted for (e.g., as in [19]). Additionally, experimental sessions lasted less than one hour.…”
Section: Study Limitationsmentioning
confidence: 99%
“…As a consequence, by measuring the intensity of the reflected light, NIRS technologies can be used to examine regional cortical activity with depths of up to 2 cm [10]. Previous research has shown that NIRS can be used to assess hemodynamic responses in the motor cortex using activities such as motor imagery [3,7], as well as in the prefrontal cortex using higher cognitive tasks such as mental arithmetic [6,11,12], working memory [13,14], and emotion induction [15,16], both in silent (e.g., [17,18]) and noisy environments [19].…”
Section: Introductionmentioning
confidence: 99%
“…(2.6) during the measurement simulation. Although fNIRS systems are a lot less sensitive to movement than fMRI, this type of artefact can cause problems and methods for motion artefact removal are an active research area [16,47,48].…”
Section: Synthetic Signal Generationmentioning
confidence: 99%
“…In ERS/ERD analysis, a baseline "reference" period of EEG data is recorded before the event and then compared to an "activity" period of EEG data, recorded during or following the event. ERD is known to occur in the frequency range (8-12 Hz) on movement onset and ERS is known to occur in theˇfrequency range (12)(13)(14)(15)(16)(17)(18)(19)(20)(21)(22)(23)(24)(25)(26)(27)(28)(29)(30) following movement offset.…”
Section: Combined Eeg-fnirs Measurements In Overt and Imagined Movemementioning
confidence: 99%
“…Prominent biosignals that are visible in fNIRS include respiration (0.2-0.4 Hz) and cardiac activity (blood pressure and cardiac pulse, up to 5.0 Hz). These biosignals respond to various tasks, such as isometric pinching [6] and music imagery [7], as part of the autonomic nervous system (ANS) response. The cortical hemodynamics respond at low frequencies (up to 0.2 Hz), so band-pass filters can remove faster signals [5] but do not remove in-band biosignal contributions.…”
Section: Introductionmentioning
confidence: 99%